Industry 4.0: Experience of Eastern European Countries and Challengers for Ukraine - Шейко, І. А.; Стороженко, О. В. (My University, 2018)
The article deals with questions of digitazation of the economy. The main theoretical aspects about industry 4.0 were indicated. The experience of Eastern European countries was considered, the classification of the EU countries according to the level of readiness for the introduction of digital technologies was given. The matrix of SWOT-analysis of the prospects for implementing the industry 4.0 in the reality of industry in Ukraine was created. В статті розглядаються питання цифровізації економіки. Означені основні теоретичні аспекти щодо індустрії 4.0. Розглянутий досвід східноєвропейських країн, наведена класифікація країн ЄС відповідно до рівня готовності до впровадження цифрових технологій. Створена матриця СВОТ-аналізу перспектив впровадження технологій індустрії 4.0 у реалії промисловості України.
Keywords: digital economy; цифрова економіка; digitalization; automation; industry 4.0; Internet of Things; SWOT analysis; цифровізація; СВОТ-аналіз